The Dimensions of Organizational Intelligence in Romanian Companies – A Human Capital Perspective - Viorel Lefter; Mihaela Prejmerean; Simona Vasilache (Theoretical and Applied Economics, 2008)
The paper discusses the perceptions of organizational intelligence dimensions in Romanian companies, taking into account the degree of awareness employees have, in relation to this concept, and the overall investments in R&D at the industry level. Starting from the concept of organizational intelligence, the way it is defined in recent literature, we establish seven dimensions which are relevant for its analysis, and test them on a relevant sample, random stratified, of Romanian companies, reflecting the structure of Romanian economy, and all the layers of company size. We examine, thus, the correlation between the quality of the organizational human capital (the individual intelligence) and the learning processes, at the organizational level. The results of the study can be further expanded to analyses of the regions of development, by correlating the dimensions of the organizational intelligence with the macro-economic, developmental indicators.